Peran orang tua dalam peningkatan pembelajaran karakter anak usia dini dalam keluarga - Mansyur, Nur Aini (Maliki Interdisciplinary Journal, 2023)
Parents play an important role in developing the potential of children. They act as the primary educators in the process of formation within the family environment. Character education is a learning approach centered around the formation of character values in an individual. The importance of character education in early childhood is significant, as during this period, a child's development progresses rapidly. This age is suitable for teaching character values based on their developmental stage. This study aims to describe the role of parents in enhancing character education in young children within the family.